2017
DOI: 10.18488/journal.1/2017.7.1/1.1.63.84
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital in Selected Business Associations of Food Processing SMEs in Tanzania and Rwanda: A Synthetic Based Approach

Abstract: Contribution/ OriginalityThis study contributes in the existing literature by comparing social capital in business set-up in countries belonging to the same regional block. Available literature concern largely with measuring it at the aggregate national and cross-country frameworks in informal groupings, political and democratic aspects lacking focus on business and regional orientations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Likewise, Tundui and Tundui (2013) showed that especially bridging social capital affected the profitability of women-owned businesses thus suggesting it is important for these entrepreneurs to establish linkages beyond their immediate local environment. Alternatively, Gamba (2017) recently showed that the level of trust, collective action and information sharing Tanzanian trade associations are significantly lower compared to the similar associations in Rwanda. While it is unclear to what extent these findings would be extendable to other business associations, the implication of these findings might be that Tanzanian entrepreneurs are benefiting insufficiently from existing network structures.…”
Section: Social Capitalmentioning
confidence: 96%
“…Likewise, Tundui and Tundui (2013) showed that especially bridging social capital affected the profitability of women-owned businesses thus suggesting it is important for these entrepreneurs to establish linkages beyond their immediate local environment. Alternatively, Gamba (2017) recently showed that the level of trust, collective action and information sharing Tanzanian trade associations are significantly lower compared to the similar associations in Rwanda. While it is unclear to what extent these findings would be extendable to other business associations, the implication of these findings might be that Tanzanian entrepreneurs are benefiting insufficiently from existing network structures.…”
Section: Social Capitalmentioning
confidence: 96%
“…As family members are the partners of the business, they meet and discuss the matters related to business challenges. Further, Gamba [83] noted that participation in business and technology associations by the SMEs increase their market value because it provides opportunities with the SMEs to learn lessons on business and technological challenges, and find new business techniques and new and adaptable technologies, which eventually lead to minimize the cost and increase production efficiency, improve the quality, and increase the production quantity. Moreover, the making relationship among the SMEs through clustering provide opportunities to the SMEs to make entry barriers if vital business information and techniques are available only for the SMEs in the cluster [84].…”
Section: Social Capital Approachmentioning
confidence: 99%
“…The results of the analysis of the path difference between the Manager's Interest groups are shown in [ Table 7] and [ Figure 4]. As a result of the hypothesis test, it was verified that the group with a high manager's interest in smart work activation was more influential than the group with a low manager's interest, and the quality of life was 82%, which greatly influenced the organizational performance (Fibriasari, 2019); (Gamba, 2017).…”
Section: Confirmatory Factor Analysis Intensive Validity and Reliabimentioning
confidence: 94%